ANÁLISE DA LOGÍSTICA DE PRODUÇÃO DE UMA INDÚSTRIA DE PRÉ-MOLDADOS DE CONCRETO - Santos, Marcelo Martins dos; Sousa, Lorrayne Correia; Araújo, Renato Costa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Civil Construction presents a great potential for development under the light of Information Technology applied to logistics, benefiting the level of communication between departments of a company and, consequently, the quality of information and services. In relation to precast concrete, the communication between the departments of work construction and production is extremely important for meeting deadlines, as described in the installation and manufacturing timetables. It was studied a precast concrete company (Mold Structures, mentioned as Company X) and a particular civil engineering work (Work A) executed by this company, which facilitated the practical understanding of the content that is approached in the topics of this research. Throughout the research's development, it is noticed the importance of communication at all company levels: operational, executive (tactile) and strategic. At the end of this project, it is presented a flowchart map that enables the visualization of the processes involved in the production of precast concrete.